Polycomb Repressive Complexes: Shaping Pancreatic Beta-Cell Destiny in Development and Metabolic Disease - Varghese, Sneha S.; Dhawan, Sangeeta (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic beta-cells secrete the hormone insulin, which is essential for the regulation of systemic glucose homeostasis. Insufficiency of insulin due to loss of functional beta-cells results in diabetes. Epigenetic mechanisms orchestrate the stage-specific transcriptional programs that guide the differentiation, functional maturation, growth, and adaptation of beta-cells in response to growth and metabolic signals throughout life. Primary among these mechanisms is regulation by the Polycomb Repressive Complexes (PRC) that direct gene-expression via histone modifications. PRC dependent histone modifications are pliable and provide a degree of epigenetic plasticity to cellular processes. Their modulation dictates the spatio-temporal control of gene-expression patterns underlying beta-cell homeostasis. Emerging evidence shows that dysregulation of PRC-dependent epigenetic control is also a hallmark of beta-cell failure in diabetes. This minireview focuses on the multifaceted contributions of PRC modules in the specification and maintenance of terminally differentiated beta-cell phenotype, as well as beta-cell growth and adaptation. We discuss the interaction of PRC regulation with different signaling pathways and mechanisms that control functional beta-cell mass. We also highlight recent advances in our understanding of the epigenetic regulation of beta-cell homeostasis through the lens of beta-cell pathologies, namely diabetes and insulinomas, and the translational relevance of these findings. Using high-resolution epigenetic profiling and epigenetic engineering, future work is likely to elucidate the PRC regulome in beta-cell adaptation versus failure in response to metabolic challenges and identify opportunities for highly specific therapeutic interventions.